Phytoplankton Fuel Fish Food Webs in a Low-Turbidity Temperate Coastal Embayment: A Stable Isotope Approach - Kundu, Goutam Kumar; Kim, Changseong; Kim, Dongyoung; Bibi, Riaz; Kim, Heeyong; Kang, Chang-Keun (Frontiers in Marine Science, 2021)
Trophic contributions of diverse OM sources to estuarine and coastal food webs differ substantially across systems around the world, particularly for nektons (fish, cephalopods, and crustaceans), which utilize basal resources from multiple sources over space and time because of their mobility and feeding behaviors at multiple trophic levels. We investigated the contributions of putative OM sources to fish food webs and assessed the spatiotemporal patterns, structures, and trophic connectivity in fish food webs across four seasons from three closely spaced (10–15 km) sites: an estuarine channel (EC), a deep bay (DB), and an offshore (OS) region in Gwangyang Bay, a high-productivity, low-turbidity estuarine embayment off the Republic of Korea. While nearly all previous studies have focused on few representative species, we examined 13C and 15N values of whole nekton communities along with dominant benthic macro-invertebrates, zooplankton, and their putative primary food sources. The 13C and 15N values coupled with MixSIAR, a Bayesian mixing model, revealed that these communities utilized multiple primary producers, but phytoplankton comprised the primary trophic contributor (46.6%–69.1%). Microphytobenthos (15.8%–20.4%) and the seagrass Zostera marina (8.6%–19.8%) made substantial contributions, but the role of river-born terrestrial organic matter was negligible. Spatially different species composition and stable isotope values, but higher utilization of coastal phytoplankton by estuarine fish, indicated disparate food webs structures between the EC and DB/OS coastal areas, with considerable trophic connectivity. Greater overlaps in fish and cephalopod isotopic niches than among other consumers and a higher estimated carbon trophic enrichment factor for EC nektons confirmed feeding migration-mediated biological transport of coastal OM sources to the estuary. Further, the seasonally consistent structures and resource utilization patterns indicate that fish food webs are resilient to changes at lower trophic levels. Our results contrast with those for other highly turbid coastal systems depending highly on diversified basal sources, including exported terrestrial and wetland detritus alongside autochthonous phytoplankton. Finally, this study provides a novel perspective on the role of OM sources in such low turbidity and highly productive coastal embayments and enhances our understanding of marine ecosystems.